Analisis Kesalahan Siswa Berdasarkan Kategori Kesalahan Menurut Watson dalam Menyelesaikan Soal Komunikasi Matematis Siwa SMP - Nurul Munawaroh; Euis Eti Rohaeti; Usman Aripin (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study was conducted by giving a five description test that has been validated to one of the upper classes. This research was conducted in class VII J SMP NEGRI 1 CILAMAYA WETAN with limited subject ie 6 students with high, medium, and low grade student classification. The results of the research were students' answers analyzed by the Watson error category. And the percentage of student error type in solving the problem of mathematical communication based on categories of error according to Watson is (inappropriate data/ ID) including into error which is high enough that is equal to 38%, (inappropriate procedure/IP) including into error which is quite high at 34%. (omitted conclution/OC) error is included to a fairly low error of 26%. While (ommited data/OD), (response level conflict/RLC), (undirected manipulation/UM), (skills hierarchy problem/SHP), and (above other / AO) of 0% each, including into very low errors.